Metodologi Ekonomi Islam - M. Dawam Raharjo (Universitas Islam Indonesia, 1998)
Studies and research about Islamic economics have been growing quiet fast recently. The problem is that there are not enough literature, data and fund to support the studies. Therefore, it seems to be positive that we found an Association of Islamic economics observer to support communication between observers in developing Islamic economics and local economic.